PENGARUH CORPORATE GOVERNANCE, KINERJA LINGKUNGAN DAN KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN DENGAN PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY SEBAGAI VARIABEL MODERATING (STUDI PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BEI PERIODE 2012-2014) - Zabetha, Olinsca; Tanjung, Amries Rusli; Savitri, Enni (Jurnal Ekonomi, 2018)
This purpose of this research is to test the influence of Corporate Governance,Environmental Performance, Financial Performance on Firm Value with Corporate Social Responsibility Disclosure as Moderating Variable. The population of this research are 37 Mining companies listed on Indonesia Stock Exchange during 2012-2014. The sampling method used in this research is purposive sampling, so that obtained 18 companies as sample. This research uses secondary data obtained in the form of annual reports, sustainable reporting reports and reports of proper assessment results. The method of analysis used is moderated regression analysis. The result of hypothesis testing found that managerial ownership and the proportion of independent commissioner have an effect on firm value, while environmental performance and financial performance have no effect on firm value. Corporate social responsibility disclosure is able to moderate managerial ownership and the proportion of independent commissioners to firm value, while corporate social responsibility disclosure is unable to moderate environmental performance and financial performance to firm value. The results of this research found that managerial ownership, the proportion of independent commissioner, environmental performance, financial performance and corporate social responsibility disclosure affect the company's value of 44.4%. While the remaining influenced by other variables.